2007
DOI: 10.1152/ajpheart.00448.2007
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and vasodilator effects of nociceptin/orphanin FQ in the rat mesenteric microcirculation are mediated by histamine

Abstract: ]N/OFQ-NH2 (UFP-101; 60 and 150 nmol/kg iv), H1 and H2 antagonists pyrilamine (mepyramine, 1 mg/kg iv) and ranitidine (1 mg/kg iv), and mast cell stabilizer cromolyn (1 mg⅐kg Ϫ1 ⅐min Ϫ1) also abolished vasodilation and macromolecular leak to N/OFQ in vivo (P Ͻ 0.05), but did not affect hypotension. Isolated mesenteric arteries (ϳ200 m, n ϭ 25) preconstricted with U-46619 were also mounted on a pressure myograph (60 mmHg), and both intraluminally and extraluminally administered N/OFQ (10 Ϫ5 M) caused dilation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…Interestingly, we found Orphanin protein expression mainly in the vascular compartment, in the endothelium and in the longitudinal musculature of www.fhc.viamedica.pl the vessels. In the literature, there have been many studies concerning the role of Orphanin in vasorelaxation: proinflammatory and vasodilatation effects have been reported in the rat mesenteric microcirculation and Orphanin relaxed the porcine coronary arterial rings, as well as inhibiting PGF-2a-induced vasocontractility [20][21][22]. The Orphanin expression we identified in the vascular compartment of the umbilical cord suggests a role for this peptide in the regulation of vascular tone in this organ.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 67%
“…Interestingly, we found Orphanin protein expression mainly in the vascular compartment, in the endothelium and in the longitudinal musculature of www.fhc.viamedica.pl the vessels. In the literature, there have been many studies concerning the role of Orphanin in vasorelaxation: proinflammatory and vasodilatation effects have been reported in the rat mesenteric microcirculation and Orphanin relaxed the porcine coronary arterial rings, as well as inhibiting PGF-2a-induced vasocontractility [20][21][22]. The Orphanin expression we identified in the vascular compartment of the umbilical cord suggests a role for this peptide in the regulation of vascular tone in this organ.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 67%
“…UFP-101was used in similar doses to previous studies in a mg/kg conversion dose for mice [3,6]. The non-peptide NOP antagonist SB-612111 (Tocris, UK) was dissolved in ethanol and diluted with PBS (final concentration of ethanol in 1ml injection ~2.5%).…”
Section: Methodsmentioning
confidence: 99%
“…This system has been linked to many aspects of inflammation and sepsis [10] and has been shown to modulate the cellular response to inflammatory stimuli in animals and humans [12]; in a rat caecal ligation and puncture (CLP) experimental model of sepsis, the administration of exogenous N/OFQ increased mortality whilst NOP receptor blockade significantly reduced mortality [3]. We want to establish an animal model of sepsis that is suitable to evaluate both gene expression changes in NOP and pp/N/OFQ mRNA, and the effects of nociceptin system modulation on survival.…”
Section: Introductionmentioning
confidence: 99%
“…Using fluorescent intravital microscopy, we found that N/OFQ-induced macromolecular leak could be inhibited by H1 and H2 receptor antagonists or by UFP-101. 18 UFP-101 is a peptide antagonis that is selective for the NOP receptor. 19 We also found that N/OFQ elicited other inflammatory responses such as vasodilation (also inhibited by the above antagonists) and increased rolling and adhesion of leucocytes on the endothelium 18 .…”
mentioning
confidence: 99%
“…22 This suggests that N/OFQ is involved in the upregulation of adhesion molecules such as MAdCAM-1, which binds to lymphocytes and eosinophils) Evidence from our group shows that N/OFQ also upregulates the b2-integrin CD18/CD11b adhesion molecule on rat neutrophils. 18 Increased interactions of neutrophils and other leucocytes within the microvasculature could lead to vascular occlusion. 23,24 Therefore, one of the mechanisms by which N/OFQ could be contributing to the hypoperfusion and hypoxia that occurs in sepsis could be via upregulation of adhesion molecules.…”
mentioning
confidence: 99%